Percutaneous sclerotherapy using polidocanol in the treatment of aneurysmal bone cysts of extremities – a report of 28 consecutive cases - Harshwal, Raj Kumar; Kumawat, Email src Kaushal Kishore; Saini, Narender; Sehrawat, Manisha; Meena, Devi Sahay (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Aneurysmal bone cysts (ABC) are aggressive benign lesions with high rates of recurrence rendering its treatment uniquely challenging. We report the outcome in 28 consecutive patients of ABC of extremities treated with percutaneus sclerotherapy using 3% polidocanol over a period of 5 years. Material and methods. In biopsy proven 28 ABC cases, Injection polidocanol 3% was used as sclerosing agent under fluoroscopy guidance. Injections were repeated at 6-week intervals till complete healing of cysts. Radiological and functional results were assessed by Rastogi et al. criteria, VAS score and Enneking scoring method. Results. 25 out of 26 patients (89.28%) displayed good clinical response with an average 2.56 injections per patients. The mean follow-up period was 17.04±7.08 months. Reduction in cyst volume (mean 6.86±1.48 to 0.71±1.48.) and VAS score (mean 6.72±1.51 to 0.56±1.08) and improvement in Enneking score (17.35±3.14 to 28.92±1.35) at last follow up was significant. No recurrence was reported during the study period. Treatment failure, skin sclerosis and infection were reported in one case each. Conclusion. sclerotherapy with polidocanol 3% for primary ABC is safe and effective alternate method with advantage of no surgical morbidity, having better functional score with lesser recurrence and minimal complications.
The protocol was approved by the institutional Ethics Committee (SMS Medical College Jaipur (IEC NO. 1124/MC/EC/2015).
Keywords: aneurysmal bone cysts; Enneking score; polidocanol 3%; recurrence; sclerotherapy